Clinical optochin resistant Streptococcus pneumoniae and Streptococcus pseudopneumoniae strains in Tunisia - Sonia Ktari; Nour El Houda Ben Ayed; Sonda Maalej; Basma Mnif; Faouzia Rhimi; Adnene Hammami (Journal of Infection in Developing Countries)
Introduction: Streptococcus pneumoniae can be responsible for severe human infections. Optochin resistance has been a potential cause of misidentification of pneumococcus and other members of the mitis group. Hence, rapid and easy optochin resistant (Optr) S. pneumoniae identification is essential.